Companion to literary myths, heroes and archetypes - Brunel, Pierre; Allatson, Wendy; Hayward, Judith; Selous, Trista (New Fetter Lane, London Routledge, 1992)
This collection of fascination essays explores the nature and influence of myth and mythic figures in the context ofliterature. Each essay traces the life of a particular myth in fiction, poetry or drama, drawing on legends from all over the world, from prehistory to the modern age. Alphabetically organized, the Companion's entries fall largely into four main areas: the Cosmos, the Psyche, Society, and History/ Politics.--[book cover]
First published in French as Dictionnnaire des Mythes Litteraires by Editions du Rocher, Jean-Paul Bertrand Editeur, Paris in 1988.
Includes bibliographical references (pages 1187-1210) and index.
Keywords: Mythology -- Dictionaries; Mythology in literature; Literatura y mitología; Mitologia .